Remarks by World Bank Group President David Malpass at Fragility Forum 2022 : Development and Peace in Uncertain Times - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at Fragility Forum 2022, Development and Peace in Uncertain Times on March 7, 2022. He said that there are no words to express the horror of the Ukrainian people, and the World Bank Group is doing everything it can to assist Ukraine and the region. He spoke about the largest refugee flow in Europe since WW2. He explained that they are assessing the consequences and how the WBG can respond, both in eastern Europe and in fragile countries around the world. He was hoping this fragility forum will confront challenges and provide new ideas on how the international community can more effectively help people facing conflict and fragility. He mentioned the following: (i) first, we are living in a world where protracted armed conflict keeps increasing, as we have seen in the Middle East and Africa, where immensely destructive impacts are reversing decades of progress in development; (ii) second, the pandemic has hit societies that are already in turmoil, food systems that are already impacted by climate change, and populations already displaced by conflict; (iii) third, climate change is a threat multiplier, placing major strain on economies and societies, particularly in fragile settings; and (iv) equally worrying are the new acute and destabilizing political crises, including coups d’états, as well as the unfreezing of old conflicts and the emergence of new inter-state wars. He highlighted that the World Bank Group has been active in fragile settings from our very inception and the support to countries affected by fragile, conflict, and violence (FCV) has deepened over the last decade. He spoke about their current FCV strategy provides a basis for differentiating their response at every stage of fragility and conflict as follows: helping prevent or mitigate risks in fragile environments; ensuring that they remain engaged in active crises and conflicts; and working to ensure sustainable recovery in post-crisis transitions. He hopes that the discussions during the Forum will help deepen our understanding of challenges related to fragility and set the concrete actions and priorities for the international community, for governments, and for people working to reverse the alarming trends we are seeing now.